2007
DOI: 10.1002/dvdy.21387
|View full text |Cite
|
Sign up to set email alerts
|

Patterning the embryonic kidney: BMP signaling mediates the differentiation of the pronephric tubules and duct in Xenopus laevis

Abstract: The Bone morphogenetic proteins (BMPs) mediate a wide range of diverse cellular behaviors throughout development. Previous studies implicated an important role for BMP signaling during the differentiation of the definitive mammalian kidney, the metanephros. In order to examine whether BMP signaling also plays an important role during the patterning of earlier renal systems, we examined the development of the earliest nephric system, the pronephros. Using the amphibian model system Xenopus laevis, in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 86 publications
(113 reference statements)
1
16
0
Order By: Relevance
“…A recent report showed that blocking this pathway during Xenopus neurula stages impaired pronephros formation (Bracken et al, 2008). These results resemble those observed by reducing Irx function.…”
Section: Rescue Of Irx-dependent Kidney Defects By Increasing Bmp Sigsupporting
confidence: 65%
See 1 more Smart Citation
“…A recent report showed that blocking this pathway during Xenopus neurula stages impaired pronephros formation (Bracken et al, 2008). These results resemble those observed by reducing Irx function.…”
Section: Rescue Of Irx-dependent Kidney Defects By Increasing Bmp Sigsupporting
confidence: 65%
“…Thus, one possible mechanism of action of Irx proteins could be to 3205 RESEARCH ARTICLE Irx genes in Xenopus kidney development upregulate Bmp signalling, which is known to participate at many steps during vertebrate kidney formation (Cain et al, 2008). Consistent with this idea, the reduction of Bmp signalling during Xenopus neurula stages causes defects similar to those produced by Irx gene impairment (Bracken et al, 2008). Furthermore, we show that increasing Bmp signalling partially rescue the kidney defects observed in Irx morphant and that Bmp7 expression is downregulated in Irx-deficient embryos.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the induction of the opposite process (MET), characterized by the upregulation of ephitelial junctional components and morphological transformation into ephitelial-like colonies, seems to be a crucial step in the reprogramming process. It was suggested that BMP signal synergized with the Yamanaka factors to induce the expression of miR-200 family, that are well known to promote MET and reprogramming, also in absence of BMP signalling (Bracken et al, 2008;Gregory et al, 2008;Korpal et al, 2008) and to inhibit loss of pluripotency of mESCs in differentiating conditions (Lin et al, 2009).…”
Section: Role Of Tgf     Signalling In Reprogrammingmentioning
confidence: 99%
“…Therefore, XC3H-3b may regulate tubulogenesis by means of JNK/MAPK signaling during Xenopus pronephros development. FGF and BMP are also reported to regulate pronephros development (Urban et al, 2006;Bracken et al, 2008). The FGF signal is necessary for the condensation and transition of the nephric mesenchyme during early tubulogenesis, and the BMP signal is suggested to regulate the differentiation of the tubule and duct.…”
Section: In Vitro Differentiation Of Pronephros and Molecular Analysimentioning
confidence: 99%